Intraosseous epidermoid cysts of adjacent digits in a dog - Vagias, Michail (BMC Vet Res, 2020)
BACKGROUND: Intraosseous epidermoid cyst (IEC) is a rare, non-neoplastic, pathology in animals and humans that most commonly affects the distal phalanx. In dogs, it is important to differentiate this lesion from malignant digital tumours causing bone lysis. In previous reports, IEC has been described to affect only a single digit at the time of diagnosis which is usually based on histopathology. This is the first case report to describe immunohistochemically confirmed IECs affecting simultaneously multiple digits. CASE PRESENTATION: A 4-and-a-half-year-old female spayed Great Dane was presented with a 2-month history of progressive swelling of the distal phalanx (PIII) of digits IV and V of the right pelvic limb. Eleven weeks prior to presentation, the dog had a low-grade cutaneous mast cell tumour completely excised from the craniolateral base of its left pinna. A history of trauma to 1 of the nails of the same pes 4 years prior to referral was also reported. Examination of the right pelvic limb identified firm non-painful swelling of PIII of digits IV and V, with concurrent deformation of the nails. Radiographs of the right pes obtained by the primary veterinarian identified an expansile lesion of PIII of digits IV and V. Computed tomography identified large expansile lesions of PIII of digits IV and V, with associated cortical thinning and soft tissue swelling. Neoplasia was considered the most likely radiographic diagnosis. Histopathology of Jamshidi bone biopsies was consistent with intraosseous epidermoid cyst, which was confirmed with immunohistochemistry. Amputation of PIII of digits IV and V at the level of mid-PII was performed as definitive treatment. No recurrence of the lesion occurred during the 10-month follow-up period. CONCLUSIONS: Intraosseous epidermoid cysts should be included in the differential diagnosis for expansile lesions affecting the canine digit. It is important to differentiate them from other digital lesions, with bone involvement, such as malignant digital tumours, which often require more extensive surgery for definitive treatment. The case herein highlights that this lesion can affect simultaneously multiple digits. Definitive diagnosis can be achieved by identification of keratin-producing epithelial cells on histopathology and confirmed by pancytokeratin labelling.